2010
DOI: 10.1590/s0102-09352010000400007
|View full text |Cite
|
Sign up to set email alerts
|

Influência do butorfanol sobre os períodos de latência e de ação da ropivacaína pela via peridural na ovariossalpingo-histerectomia em cadelas

Abstract:  RESUMOAvaliaram-se os períodos de latência e de duração do efeito do butorfanol associado à ropivacaína aplicados pela via peridural e a possibilidade de uso dessa associação como protocolo anestésico para realização de ovariossalpingo-histerectomia (OSH) em cadelas. Utilizaram-se 16 cadelas pré-medicadas com acepromazina e midazolam compondo dois grupos: no grupo 1 (n=8) aplicou-se ropivacaína isolada (0,3mL/kg) e no grupo 2 (n=8), butorfanol (0,1mg/kg) e ropivacaína (até o volume de 0,3mL/kg), pela via per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Furthermore, increases in those variables contributed for compensating hypoventilation, which caused high PaCO 2 values. When comparing epidurally administered tramadol with morphine in dogs, Baraka et al (1993) have reported significant respiratory changes such as decreased f R and PaO 2 without variations in PaCO 2 when morphine was used. In one retrospective study of 242 dogs and 23 cats, epidural anesthesia with morphine with or without bupivacaine has been associated with respiratory alterations that decreased P E´C O 2 and increased PaCO 2 (Troncy et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, increases in those variables contributed for compensating hypoventilation, which caused high PaCO 2 values. When comparing epidurally administered tramadol with morphine in dogs, Baraka et al (1993) have reported significant respiratory changes such as decreased f R and PaO 2 without variations in PaCO 2 when morphine was used. In one retrospective study of 242 dogs and 23 cats, epidural anesthesia with morphine with or without bupivacaine has been associated with respiratory alterations that decreased P E´C O 2 and increased PaCO 2 (Troncy et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The onset time and duration of the blockade were determined according to Albuquerque et al (2010). Analgesia at the postoperative period was assessed through visual analog scale (VAS) for pain.…”
Section: Methodsmentioning
confidence: 99%
“…It is capable of providing analgesia and muscle relaxation in the retroumbilical region (SOUZA et al, 2013) and causes minimal cardiorespiratory changes. It also improves control over postoperative pain, reduces transoperative stress (ALBUQUERQUE et al, 2010), is safe and efficient, and can reduce the concentration of inhaled anesthetic required for the maintenance of proper anesthesia (VALVERDE, 2008;ITAMI et al, 2011;BOSMANS et al, 2011;NATALINI et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Ropivacaine, a pure S enantiomer, provides significant advantages over its precursor, bupivacaine, including reduced motor nerve blockade, lower-intensity action on the fibers responsible for motor action, and lower cardiotoxicity. However, its use is limited because of its high cost ( VAN DE VELDE et al, 2007;SILVA et al, 2008;ALBUQUERQUE et al, 2010;SOUZA et al, 2013). Local anesthetics, which produce sensory block and immediate engine, when combined with ED opioids, increase the duration and intensity of analgesic effect, contributing to the acceleration in the postoperative recovery of the animal (VALADÃO et al, 2002;BASSO et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation